A Review on Potential of Quarry Dust Waste as An Aggregate in Concrete Production - Abdull Bakar, Akmal Zharif; Ahmad Jeni, Mohamad Luthfi (Progress in Engineering Application and Technology, 2021)
A serious environmental problem is quarry dust, which is produced in large amounts from quarries. In construction applications, the use of these materials may lead to both economic and environmental benefits. This paper reviews recent research studies on the development of concrete materials, either as aggregates or as substitute materials for cement. Therefore, for this study, quarry dust waste will be used as the replacement of aggregate in concrete production. The aim for this research is to discover the potential and the mechanical properties of the quarry dust waste as a replacement of aggregate in concrete. The slump test, compressive strength test, flexural test and split tensile strength are the mechanical properties highlighted in this report. Both detail and data are taken from previous research articles. Different percentage replacement of aggregate into the concrete is proven to give the concrete different mechanical efficiency. It is found that 40% replacement of fine aggregate by quarry dust gives maximum result in strength than normal concrete and then decreases from 50%. The compressive strength is quantified for varying percentage and grades of concrete by replacement of sand with quarry dust.